2014
DOI: 10.11648/j.sjcm.20140301.13
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Radiation Exposure of Head and Neck during Panoramic Radiography in Different Age Groups

Abstract: Background and aim: Panoramic imaging is one of the most commonly used imaging techniques in dentistry.Being able to accurately assess the radiation dose patients receive during procedures is a crucial step in the management of dose. The main objective of this study was to evaluate the head and neck skin absorbed dose during panoramic radiography in different age groups with panoramic machine of Oral and Maxillofacial Radiology section of Babol school of dentistry. Materials and methods: 273 thermoluminescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…Together with the reviewed evaluations of organ-specific sensitivity, the salivary gland and Oral mucosa doses will have a main influence on the effective dose (14) . Contrary to the results of the present study, another study (16) show that, utmost of the skin absorption dose goes to parotid was (0.23 ± 0.15 mGy) using panorama.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Together with the reviewed evaluations of organ-specific sensitivity, the salivary gland and Oral mucosa doses will have a main influence on the effective dose (14) . Contrary to the results of the present study, another study (16) show that, utmost of the skin absorption dose goes to parotid was (0.23 ± 0.15 mGy) using panorama.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, CBCT has been commonly used in dental clinics since more than ten years. The radiation dose to the patient is also becoming a main concern, despite the fact that the profits of CBCT have been reported generally (1,16) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is obvious that the mean skin dose values in the present study are lower than those identified in Lorestan province (19) and Mashhad city (6) . But, these numbers are higher compared to Isfahan (20) and Babol cities (21) . The differences can be related to the use of various exposure factors during the panoramic examinations.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, measuring the dose delivered to patients in various radiographic tests and optimizing the image quality, and dose to reduce the risk of radiation exposure are very important. Thermoluminescence dosimetry has always been one of the effective dosimetry methods for estimating doses in diagnostic radiology, nuclear medicine and radiotherapy [14][15][16][17][18][19][20]. The purpose of this study is to estimate the entrance skin dose and the doses received by various organs in OPG imaging.…”
Section: Introductionmentioning
confidence: 99%